Using Direct-to-Consumer Genetic Testing Results to Accelerate Alzheimer’s Disease Clinical Trial Recruitment - Ryan, Mary M. (Alzheimer Dis Assoc Disord, 2021)
INTRODUCTION: The apolipoprotein E (APOE) gene is the strongest known genetic risk factor for sporadic Alzheimer’s disease (AD). APOE can be used as an enrichment strategy or inclusion criterion for AD prevention trials. Personal genomics companies market direct-to-consumer (DTC) genetic tests, including APOE. We assessed DTC APOE testing usage among enrollees of the UC Irvine Consent-to-Contact Registry, an online recruitment registry, and attitudes toward using this information in clinical trial recruitment. METHODS: We emailed links to an electronic survey to registry enrollees age 50 years or older. We assessed participants’ use of DTC services, willingness to learn APOE status, and willingness to share genetic information. Logistic regression models assessed relationships between DTC testing usage and demographic characteristics, as well as with willingness to share results to assist trial recruitment. RESULTS: Among 1,312 responders (57% response rate), few (7%) had used DTC testing for APOE. Non-Hispanic Asian enrollees were 93% less likely to have used DTC testing, compared to non-Hispanic whites (95% CI: [0.01, 0.67]). Willingness to share APOE information for study recruitment was >90% for both users and non-users. CONCLUSIONS: Matching participants to trials based on DTC APOE information may be an effective way to streamline AD prevention trial recruitment.